Analysis of Alphalactalbumin and Betalactoglobulin from the Rehydration of Bovine Colostrum Powder Using Cloud Point Extraction and Mass Spectrometry - Fan Zhang; Xiaohua Qi; Mingqiang Zou; Jinfeng Li (Journal of Analytical Methods in Chemistry)
Alphalactalbumin (α-La) and betalactoglobulin (β-Lg) in the rehydration of bovine colostrum powder were successfully separated by cloud point extraction using a nonionic surfactant Triton X-114. The effects of different factors, including the surfactant concentration, sample volume, electrolyte, and pH were discussed. The optimized conditions for cloud point extraction of alphalactalbumin (α-La) and betalactoglobulin (β-Lg) can be concluded that the best surfactant is 1% (w/v) Triton X-114, 200 μL of sample volume, 150 mmol/L NaCl, and 6% (w/v) sucrose. After cloud point extraction, the capillary electrophoresis is used to check the efficiency of the extraction procedure. The results had been effectively confirmed by the characterization with matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS).